Combined District Heating System CHP-Local Heat Pumps. Part II - Sit M.L.; Juravliov A.A.; Suvorov D.M.; Suvorova L.A. (Problems of the Regional Energetics, 2020)
The paper discusses options for district heating systems, including thermal power plants and heat pumps installed in individual heating centers of multi-story buildings. The aim of the work is to evaluate the energy efficiency of the options under consideration and the method of connecting piping to high-temperature return network water with a carbon dioxide heat pump. The goal is achieved due to the fact that one of the evaporators of the heat pump heating the new building or half of the existing building uses heat from return network water or from the first half of the building or from the whole building, and the second evaporator uses the heat of the outdoor air. Moreover, for high-temperature heating schedules, heat is taken out through a two-stage inter-mediate circuit containing two pumps, 2 heat exchangers and two expansion vessels. Significant results of the work are the developed scheme of the intermediate circuit of the carbon dioxide heat pump, which combines both the possibilities of working in a quantitative heat supply sys-tem and in the preparation of hot water for buildings during the non-heating period. The signifi-cance of the obtained results lies in the fact that the proposed technical solution allows to reduce fuel consumption for thermal power plants, consumers' expenses when paying for their con-sumed energy resources, increase the number of heat consumers connected to the thermal power plants through the use of heat pumps. The schemes of intermediate circuits of heat pumps for the quantitative law of regulating the operation mode of the heat supply system are also consid-ered.